Pengembangan Program Crafting untuk Meningkatkan Kreativitas dan Kemandirian Lansia di Panti Sosial Tresna Werdha Provinsi Bengkulu - Marrita Sari; Nengke Puspita Sari (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
This study aims to develop an effective crafting program to improve the creativity and independence of the elderlyat Panti Tresna Werdha. This study uses a program development method with a pre-test and post-test design. Thesample of this study was 30 elderly at Panti Tresna Werdha who were selected randomly. The results of the studyshowed that the crafting program can increase the creativity of the elderly by 70%, and the independence of theelderly by 60%. This study concludes that the crafting program can be an alternative activity that is beneficial forthe elderly to increase creativity and independence. Therefore, the crafting program can be implemented routinelyat Panti Tresna Werdha to improve the welfare of the elderly. The conclusion of this study is that the CraftingProgram to Increase Creativity and Independence of the Elderly at the Panti Tresna Werdha Social Institution inBengkulu Province shows that the crafting program has a significant positive impact on increasing the creativityand independence of the elderly. Through crafting activities, the elderly can not only express themselvescreatively, but also improve fine motor skills and self-confidence. In addition, this program also contributes tosocial interaction between the elderly, which is important for their mental well-being. Overall, the implementationof this program is expected to be an effective model for improving the quality of life of the elderly in socialinstitutions.